PERIODONTITIS: SYMPTOMS, CAUSES, AND TREATMENT - Nishonov Zokhidjon Khayrulla ugli; Ortikova Nargiza Khayrullayevna (Sciental Journals Publishing, 2025)
Periodontitis is an inflammation of the tissues surrounding the tooth (periodontal), followed by the destruction of the ligaments of the tooth with the bone tissue of the jaw. It is manifested by bleeding and inflammation of the gums, pain when pressed, an unpleasant odor from the oral cavity, and tooth mobility.